Improving Learning Outcomes of Invoice Driving in Football Games Through The Tgt Type Cooperative Learning Model in Class XI Students of SMK Negeri 8 Ambon - Rengil, Alvin; Latar, Idris Moh.; Matitaputty, Johanna (Peneliti.net, 2024)
This research is Classroom Action Research (PTK), which is cyclical research which aims to improve the quality of learning in the classroom on an ongoing basis (Anwar, 2018). For this reason, in order to improve the quality of football learning, especially dribbling material, researchers used a PTK design. And based on the analysis of the results of learning to herd with the instep in cycle I it was 76% and in cycle II it increased by 4% to 80%. Based on the results of research carried out over two cycles as follows: Results of learning to dribble with the instep in learning soccer through modelsTimes Games Tournames shows an increase. Thus it can be concluded that the modelTimes Games Tournamens effective for teaching dribbling with the back foot in soccer lessons for class XI students at SMK Negeri 8 Ambon.